Метонімізація західнополіських фітономенів - Омельковець, Руслана Степанівна; Omelkovets, Ruslana S. (Міжнародний гуманітарний університет, 2016)
У статті розглянуто семантичну трансформацію як наслідок метонімічних перенесень на основі ботанічної лексики західнополіських говірок, визначено основні семантичні моделі, за якими відбувається переосмислення. Встановлено, що семантичні деривати є наслідком метонімічних перенесень, які базуються на вживанні замість одного слова іншого на основі асоціативного зв’язку за просторовою, часовою чи логічною суміжністю. Виділено власне метонімію та метонімію, ускладнену деривацією.

The article deals with the lexical and topical group of the names of plants which is an ancient and worth of studying in the history of language; in particular semantic transformation as a result of metonymical changes based on botany lexics; the main semantic models are determined. It has been revealed that semantic derivatives are the result of met-onymic transference, which is characterized by the use of one wordinstead of another based on the associative connections caused by spatial, time-based or logical contiguity. The author differentiates metonymy proper and the metonymy complicat¬ed by derivation.
Metonymisation of westernpolissyan phytological nominations
Keywords: лексема; фітономени; західнополіські говірки; способи номінації; семантичні моделі; lexeme; phytological nominations; western¬polissyan dialects; methods of nomination; semantic transfor¬mation; metonymical transformation; semantic models